KEHILANGAN NITROGEN PADA SISTEM USAHATANI JAGUNG MANIS DI LAHAN GAMBUT KALIMANTAN TENGAH (Nitrogen Lost on Sweet Corn Of Peatland Farming System in Central Kalimantan): Suparto, H. 1) - Administrator Journal (Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTApplication of fertilizer can increase nitrogen loss in agricultural land in the form of leaching andvolatilization. Research carried out on peat soil, done two times planting. First in the dry season totransition with nitrogen input from urea fertilizer, cow dung manure and from rainfall. Both areimplemented in the month of transition to the rainy season with nutrient input from nitrogen derivedfrom pearl NPK fertilizer, chicken manure and rainfall. Nitrogen washing is obtained frompercolation water which is accommodated by lysimeter. The volume of percolation water measuredat plant age 15, 30, 45 HST and at harvest, N content in laboratory analysis. The purpose of thisresearch is to know total nitrogen loss and efficiency level of sweet corn farming system inpeatland. Nitrogen washing in the first study was 2.28 kg N ha-1 or 2.49% and in the second studywas 8.95 kg N ha-1 or 13.65%. The other estimated loss of volatilization in the first study was 12.80Kg N ha-1 or 13.97% and in the second study it was 6.76 Kg N ha-1 or 10.31%. Average lossestimated volatilization of 9.78 kg N ha-1 or 12.45% Total nitrogen loss of 19.60%, so that sweetcorn farming system on peatlands in Kalampangan Urban Palangkaraya is classified as inefficientKeywords: Nitrogen, Sweet Corn, Peat Land